2007
DOI: 10.1007/s00726-007-0575-3
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolinium and imidazolium chiral ionic liquids derived from natural amino acid derivatives

Abstract: Starting from commercially available amino acid derivatives, two novel families of chiral ionic liquids having either a thiazolinium or an imidazolium cation were prepared by simple and straightforward procedures in good overall yields. The properties of these new salts can be finely tuned by careful selection of the anion and the cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The formation of the imidazolium salts was indicated by the diagnostic downfield shift (Scheme 2). Formation of the complexes was supported by the disappearance of the signal for the C ε -bound proton in the 1 H NMR spectra and by the downfield shift of the carbene signal in the 13 C NMR spectra to δ C 156.9, 182.9 and 182.3 ppm for 5a, 6a and 6b, respectively. Of note, the NMR spectra of all three 50 complexes showed the presence of two rotamers, as expected from the slow rotation about the M-C carbene bond.…”
Section: Synthesis Of Alanine-based Histidylidene Metal Complexesmentioning
confidence: 96%
See 1 more Smart Citation
“…The formation of the imidazolium salts was indicated by the diagnostic downfield shift (Scheme 2). Formation of the complexes was supported by the disappearance of the signal for the C ε -bound proton in the 1 H NMR spectra and by the downfield shift of the carbene signal in the 13 C NMR spectra to δ C 156.9, 182.9 and 182.3 ppm for 5a, 6a and 6b, respectively. Of note, the NMR spectra of all three 50 complexes showed the presence of two rotamers, as expected from the slow rotation about the M-C carbene bond.…”
Section: Synthesis Of Alanine-based Histidylidene Metal Complexesmentioning
confidence: 96%
“…This coupling reaction afforded the tyrosine-containing histidinium tetrapeptide 10 as a highly hygroscopic solid. Analyses by NMR spectroscopy revealed the disappearance of the C ε H signal in the 1 H NMR spectra and the appearance of a low field doublet in the 13 C NMR spectra at δ C 182 ppm ( 1 J RhC = 51 Hz). Two sets of signals were observed, which were attributed to the presence of two rotamers.…”
Section: Synthesis Of Histidylidene Complexes Containing a Remote Potmentioning
confidence: 99%
“…22,23 Chiral ILs are a class of ILs which have chirality in cations or anions. [30][31][32][33] Recently, the study of AAILs has mainly focused on their synthesis and characterization. [24][25][26][27][28][29] Amino acid ionic liquids (AAILs) were synthesized from natural amino acids; thus, most AAILs have stereogenic centers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other chiral ILs, AAILs have many advantages, such as stable chirality, high biocompatibility, and good biodegradability, etc. [30][31][32][33] Recently, the study of AAILs has mainly focused on their synthesis and characterization. [34][35][36][37] In separation science, only a few papers focused on the application of AAILs as chiral ligands in LE-CE.…”
Section: Introductionmentioning
confidence: 99%
“…CILs are used for enantioselective separation of pharmaceutical products by capillary electrophoresis, [24] to tune some kinetics aspects on the asymmetric hydrogenation of some specific compounds [25], chiral stationary phase for the liquid chromatographic resolution [26], enantiomeric recognition properties [27], influence on the excitedstate properties [28], and others. Furthermore, the importance of CILs are reflected in various publications showing simply their syntheses, characterizations and properties [29,30,31] Several reviews can be found describing the development in the syntheses and applications of CILs [15]. In the present review we focus on the application of CILs in asymmetric catalysis and not on the synthesis/design of CILs which are more intensively discussed in previous reviews [15].…”
Section: Introductionmentioning
confidence: 99%